A database of didactic activities on climate change - Cane, Daniele; Boschis, Gianni (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2024)
The project “Ghiaccio Fragile – i cambiamenti climatici e la montagna”, now in its ninth edition, offers indepth training on climate change didactics for teachers from all over Italy. The project is composed by a Summer School (which includes field activities in the Alps of Valle d'Aosta and Piedmont) and an online training course, in which teachers receive insights of a technicalscientific nature, on the social impacts and on the political and ethical challenges of climate change. Numerous educational activities are also proposed, all of which have already been tested in the classes, and the teachers themselves are invited to share their experiences. Over time, a large number of activities and teaching sheets have been collected, proposed by both the trainers and the participating teachers. These activities are now organized into an openaccess database and this article explores and describes the contents of that database. The proposed activities are characterized by a marked interdisciplinarity and strong ties with the themes of Civics and are aimed at children of different ages, with a greater offer for students of the High School. Some activities last for a lesson or a day, others cover the entire school year; very different techniques are used, from debate to roleplaying, from field trips to Cooperative Learning.